WITS 2020 Proceedings of the 6th International Conference on Wireless Technologies, Embedded, and Intelligent Systems - Bennani, Saad.; Lakhrissi, Younes; Khaissidi, Ghizlane; Mansouri, Anass; Khamlichi, Youness; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents peer-reviewed articles from the 6th International Conference on Wireless Technologies, Embedded and Intelligent Systems (WITS 2020), held at Fez, Morocco. It presents original research results, new ideas and practical lessons learnt that touch on all aspects of wireless technologies, embedded and intelligent systems. WITS is an international conference that serves researchers, scholars, professionals, students and academicians looking to foster both working relationships and gain access to the latest research results. Topics covered include Telecoms & Wireless Networking Electronics & Multimedia Embedded & Intelligent Systems Renewable Energies.
A Hybrid Indoor Localization Framework in an IoT Ecosystem -- Current works on IDS development strategies for IoT -- New metrics to measure the quality of rankings results of the multi-criteria decision-making methods -- LiteNet : A novel approach for traffic sign classification using a light architecture -- The attitude of Moroccan university students towards an online assistive application of stress management -- Detection and Prediction of Driver Drowsiness for the Prevention of Road Accidents Using Deep Neural Networks Techniques -- A new framework to secure cloud based e-learning systems -- A term weighting scheme using fuzzy logic and domain ontology for enhancing candidate screening task -- Social diffusion and interaction strategy in social network for media institutions publications -- E-learning recommendation system based on cloud computing.
Keywords: Wireless communication systems; Mobile communication systems; Cooperating objects (Computer systems).; Computational intelligence; Electric power production; Telecommunication; Wireless and Mobile Communication; Cyber-Physical Systems; Computational Intelligence; Electrical Power Engineering; Mechanical Power Engineering; Microwaves, RF Engineering and Optical Communications; Embedded computer systems; Intelligent control systems; Congresses